Kesiapan Tenaga Administrasi Sekolah Menerima Perubahan Di Masa Pandemi Pada Sekolah Menengah Pertama Negeri Kota Solok - Sapna Anwar; Rusdinal Rusdinal; Jasrial Jasrial; Hanif Alkadri (Journal of Educational Administration and Leadership, 2022)
This research is based on the results of an interview with one of the administrative staff who implement affairs in Solok. This study aims to obtain information about the readiness of school administration staff to accept changes during the pandemic seen from 1) Mental Readiness, 2) Knowledge Readiness, 3) Participation in change. This research is quantitative descriptive. The population of this study is the administrative staff implementing affairs at the State Junior High Schools in Solok City, totaling 43 people. This research is a population study. The instrument used is a differential semantic scale questionnaire. In analyzing the data there are several steps taken, namely, data verification, data tabulation, calculating the average (mean) then looking for the percentage of achievement scores and describing the data that has been processed based on predetermined criteria. The results showed that the readiness of administrative staff to accept changes during the pandemic at public junior high schools throughout Solok City was seen from the indicators (1) Mental readiness was in the ready category with an achievement level of 83.12%, (2) Knowledge readiness was in the ready category with an achievement level (81.00). %), (3) Participation in change is in the ready category with the level of achievement (81.27%). Thus, it can be concluded that the readiness of school administration staff in accepting changes during the pandemic at State Junior High Schools throughout Solok City is in the ready category with an achievement level (81.77%).